Quality of education in Colombia - Achievements and challenges ahead : analysis of the results of TIMSS 1995-2007 - World Bank (World Bank, 2012)
The main objective of this report is to analyze the effect of time changes and factors associated with student achievement in Colombia in order to foster policies to improve education quality that are grounded in research and the Colombian context. In 2007, Colombia participated for the second time in the Trends in International Mathematics and Science Study (TIMSS), providing a first-time opportunity to analyze the effects of time changes on student achievement over a period (1995-2007) during which a number of education reforms were made. Using the TIMSS 2007 results offers a chance to deepen the study on the factors associated with learning in Colombia and to benchmark Colombia's education system against that of other countries. This effort began during the first phase of the Colombia Programmatic Quality and Relevance of Education Analytic and Advisory Activities (AAA), in which an analysis of Colombia's debut in the 2006 Program for International Student Assessment (PISA), resulted in publication of, 'the quality of education in Colombia: an analysis and options for a policy agenda' report (hereafter, 'PISA report'). The present report builds on this work through an analysis of Colombia's participation in TIMSS 2007 in relation to its performance on TIMSS 1995, and reaffirms the urgent need for improved student learning outcomes in Colombia, further confirming a number of the policy options put forward in the PISA report to inform a future agenda for system design and reform.